Translation of Aramaic Words in the New Testament Bible into Chinese - Naksit, Natthasake (Journal of Letters, 2025)
This article aims to study the translation of Aramaic words appearing in the New Testament of the Bible into Chinese. Using a case study from the New Testament of Chinese translation of the Bible (Chinese Union Bible), the research found that the Chinese translation of the Bible has four main forms of translation for Aramaic words among the Greek text of the New Testament; Transliteration with an explanation of meanings according to the original text, Transliteration without any meaning explained, Transliteration with an explanation of meanings which do not appear in the original text, and Translate only the meaning of the words. Comparing with the principles of translating scriptures that indicate that they adhere to the original’s accuracy, it has been found that the translation of Aramaic words in the New Testament has a variety of translation standards. Not only one principle, but adjust translation format to suit the content and context.